State-funded Support of International Trade in Rights and Licenses: Translation Funding Programs of Guests of Honour Argentina and France at the 2010 and 2017 Frankfurt Book Fair - Hertwig, Luise (Mémoires du livre / Studies in Book Culture, 2020)
This comparative and transnational study offers critical reflections on translation funding programs in connection with the international rights trade at book fairs. Focusing on the Argentinian and French translation support programs within the scope of their appearance as Guest of Honor at the Frankfurt Book Fair and against the background of the global system of translations, it explores which works, authors, genres and languages predominate in the choice of funding institutions. In addition to its function in cultural diplomacy, translation funding is seen as an effective tool in strengthening cultural diversity. Therefore, this contribution pays special attention to its impact on bibliodiversity, for example by looking at which actors among Argentinian, French and German publishers benefit from these programs.